Keberterimaan terhadap Sistem Layanan Pendidikan Inklusif sebagai Salah Satu Pilar Pembaharuan Pendidikan - Hermanto Hermanto (Dinamika Pendidikan, 2011)
The existence of individuals with special needs have long been aware of. Similarly, educational servicesfor individuals with special needs also have long existence. Speaking of education for  individuals with special needs, so was slow in Indonesia, especially when we speak of equality of educationfor them. Educational  equality in question is an inclusive education for individuals with special needs within the school system to "normal students"   in general. For that receive individual consciousness with special needs in mainstream schools should be immediately implemented as education for  all. The education departement, or school must immediately take concrete steps in an effort to inclusive education service as    trustee of Permendiknas number 70 in 2009.  The education departement or school immediately promotion, trying to find  a model or system of inclusive education services, and then apply it. The problem  is not perfect,  there are many shortcomings, or the criticism concerning the implementation of inclusive education, regarded as an input to the process of repair. With the acceptance of an inclusive system of education services, then this is one of the pillars of education reform in Indonesia.   Keyword: acceptance, Inclusive, Education Reform.